Social Interaction Among Male And Female Physical Education Teachers in Al-Majar Al-Kabeer in Maysan Governorate - Abdullah, Sadiq Ibrahim; Manati, Wissam Halil (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2025)
The importance of research lies in revealing level of social interaction of teachers of Al-Majar Al-Kabeer Preparatory School in Maysan Governorate and the extent of its reflection on their profession. Social interaction is an important process in their professional lives, and individual behavior is nothing but a phenomenon resulting from continuous interaction with individuals and what we expect from the behavior of others or their actual behavior. Thus, this interaction includes a kind of expectation on the part of all participants in it. The extent of the teacher's ability, effectiveness, and success in it is one of the most important psychological foundations in light of which it is linked to the leadership personality that is constantly searching for psychological interaction in its endeavor. It is dynamic and evolutionary, reflected through the stages of its development within him. In addition to the above, the teacher is considered a social pioneer because he feels the problems in society and works to deal with and solve these problems with his personal effort, capabilities, and creative style in communication and interaction with others to reach safety. Hence, the problem of the research came in the lack of a tool to measure social interaction among teachers of Al-Majar Al-Kabeer Preparatory School in Maysan Governorate. The researcher used the descriptive approach using the survey method for the purpose of preparing a scale of social interaction, as the research community is the male and female teachers of secondary and preparatory schools in Al-Majar Al-Kabeer Education Department in Maysan Governorate, numbering (830) teachers. The research sample was selected as (375) male teachers and (455) female teachers, and thus the percentage is (100%). They were selected according to what the research procedures require. Statistical transactions were conducted to extract the psychometric properties of the scale (validity, reliability, objectivity) and determine its standard levels. The researcher concluded that secondary school teachers The secondary schools of Al-Majar Al-Kabir Education in Maysan Governorate are characterized by social interaction.